Pendampingan Implementasi Strategi Digital Marketing Berbasis Media Sosial dalam Meningkatkan Daya Saing UMKM Desa di Era Ekonomi Digital - Ryan Suarantalla; Muhammad Ilman Nafian; Abdul Gani; Ariq Abdillah; Anggun Aprilia (Indo Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in rural areas face serious challenges regarding limited market access due to low digital literacy and minimal utilization of information technology as a marketing instrument. This community service activity aims to assist MSME actors in Lopok Village, Lape District, Sumbawa Regency, in implementing social media-based digital marketing strategies to enhance their competitiveness in the digital economy era. The implementation method employs a Participatory Action Research (PAR) approach encompassing three stages: pre-implementation (needs assessment and problem mapping), implementation (workshops and practical training), and evaluation (measurement of outcomes and follow-up actions). The activity was conducted on February 11, 2026, from 08:00 to 16:00 Central Indonesia Time (WITA) at the Lopok Village Hall and was attended by 25 MSME actors from various sectors. The results of the activity demonstrated a significant improvement in digital competence, with all participants successfully creating optimized Instagram Business accounts, 84% capable of producing visual content independently using the Canva application, and 88% demonstrating a sound understanding of digital marketing concepts. This program proves that hands-on training integrated with local needs can accelerate the digital transformation of rural MSMEs effectively and sustainably.